2021
DOI: 10.1152/ajpcell.00426.2020
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial metabolic manipulation by SARS-CoV-2 in peripheral blood mononuclear cells of patients with COVID-19

Abstract: The COVID-19 pandemic has been the primary global health issue since its outbreak in December 2019. Patients with metabolic syndrome suffer from severe complications and a higher mortality rate due to SARS-CoV-2 infection. We recently proposed that SARS-CoV-2 can hijack host mitochondrial function and manipulate metabolic pathways for their own advantage. The aim of the current study was to investigate functional mitochondrial changes in live peripheral blood mononuclear cells (PBMCs) from COVID-19 patients, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 20 publications
7
144
2
3
Order By: Relevance
“…Interestingly, pathways involved in RNA processing and chromatin accessibility (i.e., histone modification) were upregulated together with the response to viral infection, suggesting that SARS-CoV-2 may induce broad epigenetic reprogramming of the host to promote its own replication (Figures 4E and S4A; Tables S1 and S3) (Banerjee et al, 2020). In addition, we observed that genes involved in mitochondrial function and energy production were downregulated (Figures 4F and S4B; Tables S2 and S4), indicating that SARS-CoV-2 might promote a shift toward a glycolytic metabolism by suppressing mitochondrial oxidative phosphorylation, which could also favor its replication (Ajaz et al, 2021;Icard et al, 2021).…”
Section: Sars-cov-2 Reprograms Chromatin-modifying Rna Processing and Energy Metabolism Pathwaysmentioning
confidence: 87%
“…Interestingly, pathways involved in RNA processing and chromatin accessibility (i.e., histone modification) were upregulated together with the response to viral infection, suggesting that SARS-CoV-2 may induce broad epigenetic reprogramming of the host to promote its own replication (Figures 4E and S4A; Tables S1 and S3) (Banerjee et al, 2020). In addition, we observed that genes involved in mitochondrial function and energy production were downregulated (Figures 4F and S4B; Tables S2 and S4), indicating that SARS-CoV-2 might promote a shift toward a glycolytic metabolism by suppressing mitochondrial oxidative phosphorylation, which could also favor its replication (Ajaz et al, 2021;Icard et al, 2021).…”
Section: Sars-cov-2 Reprograms Chromatin-modifying Rna Processing and Energy Metabolism Pathwaysmentioning
confidence: 87%
“…While very few experimental data are available on the effect of mitochondrial fitness on infection with SARS-CoV-2 (e.g. there may be deficits in mitochondrial respiration in peripheral blood mononuclear cells of COVID-19 patients 71 ), several pieces of evidence suggest mitochondrial integrity to be crucial for the general anti-viral host defense 51 72 . In the following sections these arguments are discussed for the individual components of mitochondrial fitness.…”
Section: The Intimate Link Of Mitochondria and The Anti-viral Innate Immune Responsementioning
confidence: 99%
“…In fact, some viruses are able to alter the innate immune system in cells by increasing DRP1 s616 phosphorylation [ 68 ], which ultimately results in mitochondrial fragmentation and dysfunction [ 66 ]. Additionally, peripheral mononuclear cells showed altered mitochondrial metabolism by SARS-CoV-2 in patients with COVID-19 [ 69 ]. Moreover, the authors proposed that disease severity was positively associated with the degree of mitochondrial dysfunction in peripheral mononuclear cells [ 69 ].…”
Section: Mitochondria At the Crossroad To Viral Infectionmentioning
confidence: 99%
“…Additionally, peripheral mononuclear cells showed altered mitochondrial metabolism by SARS-CoV-2 in patients with COVID-19 [ 69 ]. Moreover, the authors proposed that disease severity was positively associated with the degree of mitochondrial dysfunction in peripheral mononuclear cells [ 69 ].…”
Section: Mitochondria At the Crossroad To Viral Infectionmentioning
confidence: 99%